Comprehensive cardiac rehabilitation and quality of life in coronary artery bypass graft patients - Van Rooy, Lynn; Coopoo, Y (SA Heart Journal, 2017)
The overall success of coronary artery bypass graft (CABG) surgery is much dependent on the postoperative rehabilitation. Cardiac rehabilitation (CR) programmes should be comprehensive and multifactorial to enhance the education and quality of life of the patient. This was a quasi-experimental and longitudinal intervention study to which 18 patients who had undergone CABG surgery were referred. Two questionnaires were administered and patients participated in a 12-week exercise programme. Significant improvements were noted in waist circumference (99.7 ± 8.3 to 97.8 ± 8.8; p=0.042), body fat percentage (22.7 ± 5.3% to 20.5 ± 4.9%; p=0.000), resting systolic blood pressure (125.7 ± 13.7mmHg to 119.7 ± 8.9mmHg; p=0.000), stairs climbed (3.6 ± 3.5 flights to 5.9 ± 4.4 flights; p=0.003), duration of exercise per week (329 ± 383.7min.wk-1 to 527 ± 482.7min.wk-1; p=0.001), kilocalories expended per session (827 ± 765kcal to 1173 ± 699kcal; p=0.001), kilocalories expended per week (2 550 ± 858kcal to 3 996 ± 1 849kcal; p=0.000), chair sit-and-reach (0.7 ± 3.4cm to 1.3 ± 3.4cm; p=0.001), up and go (6.0 ± 1.3sec to 5.1 ± 1.2sec; p=0.002), chair stand (13.4 ± 2.3 to 16.2 ± 2.3; p=0.000), maximum workload (82 ± 23.0 watt to 110 ± 29.4 watt; p=0.000), maximum duration (08:35 ± 02:41min:sec to 11:57 ± 03:51min:sec; p=0.000), physical component score (38.8 ± 6.1 to 52.1 ± 4.2; p=0.000) and mental component score (49.5 ± 8.5 to 56.9 ± 3.1; p=0.002). The findings of this study support the role of CR encompassing lifestyle intervention, education and psychological support in promoting a faster recovery of health and desired performance of the CABG patient.